EFFECT OF VARIATION OF MIXTURE LEACHATE WITH FLUID IN CATTLE RUMEN FORMATION OF BIOGAS - Edhi Sarwono; Rika Endata; Budi Nining Widarti (Reaktor, 2018)
Abstract Composting in addition to producing fertilizers also produce leachate containing organic material, the leachate can pollute the environment if not managed properly. This study uses leachate as the main substance of biogas, mixed with cattle rumen fluid as the biostarter. This study aims to determine the optimal composition of biogas and to determine the effect of variations in the raw material mixture to the volume of biogas, volatile solid, temperature, pH, and flame. The study was conducted over 43 days using three types of batch digester with a capacity of 27 L. Comparison of a mixture consisting of leachate composting organic waste with cattle rumen fluid in each digester with variations in material composition of the mixture of 70%: 30%, 50%: 50%, 100%: 0%. During the study was observed it the volume of biogas daily, daily pH, temperature daily, weekly flame test and volatile solid test every 10 days. The volume of biogas using the principle of cylinder volume and volatile solid test using USEPA 1684 method. The results show the variation of 70%:30%, which resulted in a final volume of 2.78 L of gas, as well as a decrease in the volatile solid 23.29%, 12.82% increase in the pH. In a variation of 50%:50% produces a final volume of gas that is 0.537 L, as well as a decrease in volatile solid 42.35%, 12.82% increase in the pH. Variations 100%:0% produces a final volume of gas that is 1,247 L, a decrease in volatile solid 21.83%, 5.19% increase in the pH. All three digesters are at mesophilic temperatures and produce blue flame. Based on the results of this study concluded that the composition of the mixture that are in the most optimal is composition of 70%:30%. Keywords : biogas, rumen fluid beef, lindi organic waste composting